2017
DOI: 10.1080/09513590.2017.1371691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pro-oxidant-antioxidant balance (PAB) and its association with inflammatory cytokines in polycystic ovary syndrome (PCOS)

Abstract: Chronic low-grade inflammation has been suggested as a key contributor of the pathogenesis and development of polycystic ovary syndrome (PCOS). To investigate the association between oxidative stress status and inflammatory cytokines in follicular fluid of 21 PCOS women compared to 21 women with normal ovarian function who underwent intra-cytoplasmic sperm injection. Concentration of IL-6, IL-8, IL-10, and TNF-α was measured using sandwich ELISA. Oxidative stress was examined by measuring total oxidant status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 29 publications
7
74
0
3
Order By: Relevance
“…As critical pro-inflammatory indicators, abnormal high levels of plasma TNF-α and IL-6 have been demonstrated to promote the proliferation, differentiation and maturation of follicles in PCOS patients [25][26][27]. Alteration of TNF-α in FF levels is associated with poorquality oocytes undergoing IVF which decreased rates of fertilization, embryonic development, and pregnancy outcome [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As critical pro-inflammatory indicators, abnormal high levels of plasma TNF-α and IL-6 have been demonstrated to promote the proliferation, differentiation and maturation of follicles in PCOS patients [25][26][27]. Alteration of TNF-α in FF levels is associated with poorquality oocytes undergoing IVF which decreased rates of fertilization, embryonic development, and pregnancy outcome [25].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 can reduce intra-follicular estradiol concentration, fertility and fertilizing capacity [26]. Studies have shown that pro-inflammatory cytokine (such as TNF-α and IL-6) in PCOS are significantly increased [27]. TNF-α, IL-6 and IL-10 play important role in the development of inflammation and oxidative stress [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress. Artimani et al (2018) have evaluated follicular fluid samples of 21 PCOS women compared to 21 women with normal ovarian function. The oxidative stress was examined by measuring total oxidant status (TOS), malondialdehyde (MDA), total antioxidant capacity (TAC), and thiol groups.…”
Section: Pathophysiology Of Pcosmentioning
confidence: 99%
“…Diante das alterações, as mulheres com SOP desenvolvem uma série de complicações, o que culmina com maior prevalência do aumento do peso e gordura corporal, elevação dos níveis de marcadores inflamatórios, aumento da resistência à insulina e diabetes tipo II, além de maiores chances de desenvolver a síndrome metabólica. (GROUP et al, 2004;GONZÁLEZ et al, 2012;LIM et al, 2013;THOMSON et al, 2012;BATISTA et al, 2014;YUAN et al, 2016;ARTIMANI, T. et al, 2017;BUSIAH et al, 2017;2017;DABBAGHMANESH et al, 2017). Além disso, tem sido demonstrado que mulheres com SOP apresentam maiores chances de alteração do estado emocional, de disfunção sexual, com redução da qualidade de vida e. (ELSENBRUCH et al, 2003;CINAR et al, 2011;FERRARESI et al, 2013;MOREIRA et al, 2013;EFTEKHAR et al, 2014;SHAFTI e SHAHBAZI, 2016;CESTA et al, 2017;KARJULA et al, 2017).…”
Section: Introductionunclassified